From Midwives to Childbirth Assistants (Theatrum historiae, 2006)
French enlightment came with new conceptions of physiological processes. It included also a childbirth that was relieved of magic and irrationality. One of the products of this ideology was populationism with its idea of the state organisation of health service. Attention to a mother and a child created its basics. Medicine focused on pregnancy and childbirth and it led to establishing of obstetrics as a special medical field. Later, gynaecology and pediatry were emancipated. Although medicalisation of childbirth was not direct and definite, medicine doctors took control over obstetrics in Europian countries from the middle of 20th century. Midwives were originally only a product of woman solidarity; it was institutionalized because every society tried to protect a beginning human life. Therefore the midwives became the first non-productive professional group that was reglemented by public authority. Suzerain, municipal, parish authorities and also some forward-looking individuals called for their competence during early modern times. On July 24th 1753 Maria Theresia published General health order for the Bohemian Kingdom that included the ordinance about the education and exams of midwives. In 1770 it was followed by such an order for all the monarchy which laid the fundamentals to modern health service. After these orders precise instructions for midwives were published; in the same time it was started with publishing of the textbooks for them. Some dozens of them are preserved up to this day and they are an important source to the history of this medical field and also to the history of this profession. We can reconstruct the genesis of social position of midewives and settle the requirements that were imposed on their professional ability and moral qualities. We can also use topographic and statistic manuals that say us a lot about the rate of midewives in concrete regions and about their efficiency. Very valuable but seldom preserved resources are also the booklets in which the midewives wrote about the course of concrete childbirths. This article is based upon four such booklets that come from Týn nad Vltavou, Choltice, Výpravy near Hradec Králové and Hořice (1870s-1930s). Current time has again rehabilited the personality of midewife. We can say that the development of obstetrics in the industrial countries reminds a circle: from the monopoly of midewife to the monopoly of medical doctor and from this one back again.